APOCALYPTIC LANDSCAPES: A COMPARISON OF ESCHATOLOGICAL CONCEPTS IN DANTE’S «DIVINE COMEDY» AND «THE BOOK OF ARDA VIRAF» (Journal of Oriental Studies, 2025)
Posthumous experiences, retribution for sins, and their atonement have captivated human thought since ancient times, sparking the imagination and finding expression in sacred texts that, despite temporal and socio-cultural differences, exhibit striking similarities and semantic correspondences. This observation invites a comparative analysis of texts from different religious traditions that convey similar moral messages, suggesting the possibility of a unified religious code.                                                                          This article examines a comparative study of two significant works: the Zoroastrian travelogue «Arda-Viraz-namak» and Dante Alighieri's Christian epic poem «The Divine Comedy». The aim is to explore the parallels between these texts, both of which are not only of immense artistic and literary value but also hold substantial socio-cultural influence. The relevance of this topic is particularly pronounced in the Armenian ethnocultural context, considering the proximity of Christian Armenia to Iran, the birthplace of Zoroastrianism and a major political player in the Middle East.
Keywords: sacred text; Divine Comedy; Book of Arda Viraf; afterlife; spiritual journey